Effect of Road and Railway Sound on Psychological and Physiological Responses in an Office Environment - Boya Yu; Linjie Wen; Jie Bai; Yuying Chai (Buildings, 2021)
The present study aims to explore the psychophysiological impact of different traffic sounds in office spaces. In this experiment, 30 subjects were recruited and exposed to different traffic sounds in a virtual reality (VR) office scene. The road traffic sound and three railway sounds (conventional train, high-speed train, and tram) with three sound levels (45, 55, and 65 dB) were used as the acoustic stimuli. Physiological responses, electrodermal activity (EDA) and heart rate (HR) were monitored throughout the experiment. Psychological evaluations under each acoustic stimulus were also measured using scales within the VR system. The results showed that both the psychological and the physiological responses were significantly affected by the traffic sounds. As for psychological responses, considerable adverse effects of traffic sounds were observed, which constantly increased with the increase in the sound level. The peak sound level was found to have a better performance than the equivalent sound level in the assessment of the psychological impact of traffic sounds. As for the physiological responses, significant effects of both the acoustic factors (sound type and sound level) and the non-acoustic factors (gender and exposure time) were observed. The relationship between sound level and physiological parameters varied among different sound groups. The variation in sound level hardly affected the participants’ HR and EDA when exposed to the conventional train and tram sounds. In contrast, HR and EDA were significantly affected by the levels of road traffic sound and high-speed train sound. Through a correlation analysis, a relatively weak correlation between the psychological evaluations and HR was found.